Acute effects of beta blockade and exercise on mood and anxiety. - Head, A (1996)
OBJECTIVE: To measure the previously reported beta blocker induced adverse changes in mood state and anxiety measures, and to determine if prolonged aerobic exercise attenuates such mood modifications. METHODS: After 4 days of drug treatment with comparable doses of propranolol (40 and 80 mg), metoprolol (50 and 100 mg), or placebo, mood (POMS) and anxiety states (STAI) were assessed in healthy volunteers, before and after 1 h of treadmill walking exercise at 50% maximum oxygen uptake. RESULTS: Compared to placebo, resting "tension", "depression", and "total mood disturbance" were significantly higher on propranolol 80 mg, but all were reduced with exercise. "Fatigue" and "confusion" were also higher on propranolol, and were unaffected by exercise. "Fatigue" was also higher than placebo after exercise on metoprolol 100 mg. "Anxiety" was unaffected by drug treatment or exercise. CONCLUSIONS: The evidence that beta blockers, and particularly propranolol, have adverse effects on mood was confirmed. It would be preferable to prescribe a beta blocker which does not adversely alter mood states. However, exercise significantly reduced the measures of "tension" and "depression" which were adversely increased by propranolol. Exercise prescription may therefore not only be compatible with beta blockade, but a highly desirable adjuvant therapy.